Оntology of tour of the virtual museum 3D panorama - Honchar, Andrii V.; Popova, Maryna A.; Stryzhak, Oleksandr Ye. (Kyiv National University of Construction and Architecture, 2019)
The article is devoted to the systematic and ontological analysis of the research domain and the formation on its basis of information models of knowledge formalization and knowledge presentation in modern network environments of memory institutions. The ontological approach to the formation of the ontology of tour of a virtual museum 3D panorama, which provides interactive interaction and transdisciplinary perception of objects of educational and research activities, is considered.